Case report: 18F-FDG PET confirmed pupil-sparing third nerve palsy heralding aseptic cavernous sinus embolism in patient with chest malignancy - Xiong, Jianmei; Liu, Huanbo; Li, Jianyong; Hou, Jiajia; Cui, Fang (Frontiers in Surgery, 2022)
Classical cavernous sinus embolism is a rare clinical finding, presenting most commonly with complaints of headache, diplopia, visual field defects, facial pain, and progressive neurological deficits. Many patients present with features of III, IV, and VI nerve palsies. We hereby report a quite rare case of aseptic cavernous sinus embolism developed in a 75-year-old male with primary lung cancer, who presented with binocular diplopia due to unilateral third and six cranial nerve palsies with pupil-sparing. The possibility of cavernous sinus cancer embolus should be considered if the routine examination excluded metastases, infiltration, carcinomatous meningitis or paraneoplastic process. 18F-FDG PET may provide a promising diagnostic modality for the diagnosis of cancer embolus